Morphogenesis of age groups of marandu palisadegrass tillers during the stockpiling period - Amanda Aparecida Brito; Lorena Carla Adorno; Victor Santana Novais; Gustavo Segatto Borges; Bruno Gomes Borges; Kimberly Barcelos Gois; Manoel Eduardo Rozalino Santos (Acta Scientiarum. Animal Sciences, 2022)
The stockpiled forage canopy consists of tillers at different ages, which have specific development patterns. The objective was to understand the development of Urochloa brizantha cv. Marandu during the stockpiling period, by the morphogenic evaluation of tillers at different ages. The experiment was conducted in a completely randomized design, in a split plot scheme, with four replications. Three tillers ages (young, mature and old) and two periods of stockpiling (initial and final) were evaluated. The leaf appearance and elongation rates were higher in young tillers (0.05 tiller-1 day-1 and 0.62 cm tiller-1 day-1, respectively), compared to old tillers (0.02 tiller leaf-1 day-1 and 0.20 cm tiller-1 day-1, respectively). The final leaf length of the tillers' age groups was the same in the beginning of stockpiling. The number of live leaves was lower in the old tillers (2.4), compared to the young (3.6) and mature (4.1) ones, contrary to the stem length. The number of old tillers (800 tillers m-2) was higher than the young (299 tillers m-2) and mature ones (358 tillers m-²). The participation of different age groups of tillers in the canopy influences the development and structure of marandu palisadegrass.